UNLEARNING COLONIAL IDENTITIES WHILE ENGAGING IN RELATIONALITY: SETTLER TEACHERS’ EDUCATION-AS-RECONCILIATION - Korteweg, Lisa; Fiddler, Tesa (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2018)
Before the TRC’s Calls to Action, we were a collaborative teacher-education partnership of Anishinaabekwe and White settler researching and teaching reconciliation as pedagogical practice with five cohorts of settler teacher-candidates. Engaging theories of settler-colonialism, decolonization and Indigenous studies, we outline the obstacles and struggles in settler teacher education, such as exposing the legacies of colonialism in education, cultural harms and systemic racism in curriculum, and ongoing ignorance as entitlement by teachers. In addition, we focus on the complexities of methods for improving respectful relationality with Indigenous students and community as well as our hopes in helping new teachers commit their professional practice to focus on supporting Indigenous children and youth.